Irreversible Electroporation - Narayanan, Govindarajan (Seminars in Interventional Radiology, 2015)
Irreversible electroporation (IRE) is a predominantly nonthermal ablative technology that uses high-voltage, low-energy DC current pulses to induce cell death. Thermal ablative technologies such as radiofrequency ablation, microwave ablation, and cryoablation have several applications in oncology but have limitations that have been established. IRE has shown promise to overcome some of these limitations. This article reviews the basics of the technology, patient selection, clinical applications, practical pointers, and the published data.
Keywords: irreversible electroporation; ablation; interventional radiology; liver; pancreas; prostate